Perbandingan Pengaturan Poligami di Indonesia dan Malaysia - Refo Afdhal; Umar Hasan; M. Amin Qodri (Universitas Jambi, Fakultas Hukum, 2021)
This study aims to see the comparison between two laws in two countries, namely the State of Indonesia which uses Law Number 1 of 1974 concerning Marriage, and Government Regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage and the State of Malaysia which uses Malaysian Law Deed 303. The problem is what are the similarities and differences in the arrangements for polygamy in the two countries. This type of research is normative, namely scientific research procedures to find the truth based on the logic of legal science from a normative side which is built on the basis of scientific disciplines and the workings of normative legal science. The result of this research is the arrangement of polygamy in Indonesia and Malaysia which have several similarities and differences in the arrangement of polygamy. Conclusion: The Malaysian Law Deed 303 has similarities which include enforceability, permissibility of polygamy, permission of polygamy from the court, submission of written applications, reasons for husbands to do polygamy, there are regulations regarding the requirements for polygamy, criminal sanctions, the basis for granting permission, consent of wives, conditions. -conditions, dissolution of polygamous marriage and the amount of the criminal threat. Suggestion: that in order to create legal certainty, the Indonesian government must make improvements in the regulation of polygamy and increase fines and imprisonment. Abstrak Penelitian ini bertujuan untuk melihat perbandingan antara dua hukum di dua negara yaitu Negara Indonesia yang menggunakan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, dan Peraturan Pemerintah Nomor 9 Tahun 1975 tentang Pelaksanaan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Negara Malaysia yang menggunakan Undang-Undang Malaysia Akta 303. Permasalahannya yaitu apa persamaan dan perbedaan pengaturan poligami di kedua negara tersebut. Tipe penelitian ini adalah normatif, yaitu prosedur penelitian ilmiah untuk menemukan kebenaran berdasarkan logika keilmuan hukum dari sisi normatif yang dibangun berdasarkan disiplin ilmiah dan cara-cara kerja ilmu hukum normatif. Hasil penelitian ini adalah pengaturan poligami di Indonesia dan Malaysia yang memiliki beberapa persamaan dan perbedaan dalam pengaturan poligami. Kesimpulan: dalam Undang-Undang Malaysia Akta 303 memiliki persamaan yang meliputi keberlakuan, kebolehan poligami, izin poligami dari pengadilan, pengajuan permohonan secara tertulis, Alasan Suami Melakukan Poligami, terdapatnya pengaturan mengenai persyaratan poligami, sanksi pidana, dasar pemberian izin, persetujuan istri, syarat-syarat, pembubaran perkawinan poligami dan besaran ancaman pidana. Saran: bahwa dalam rangka menciptakan kepastian hukum, pemerintah Indonesia harus melakukan perbaikan dalam pengaturan poligami dan memperberat tindak pidana denda maupun pidana penjara.